PS 13-24 POSSIBLE SYNERGISTIC EFFECT OF ROSUVASTATIN AND DIRECT ANGIOTENSIN II TYPE 2 RECEPTOR AGONIST ON CUFF-INDUCED VASCULAR REMODELING. (September 2016) - Mogi, Masaki; Bai, Hui-Yu; Nakaoka, Hirotomo; Kan-no, Harumi; Tsukuda, Kana; Shan, Bao-Shuai; Kukida, Masayoshi; Yamauchi, Toshifumi; Higaki, Akinori; Min, Li-Juan; Iwanami, Jun; Horiuchi, Masatsugu
Abstract : Objective: Here, we investigated the effect of cotreatment with rosuvastatin and compound 21 (C21), a selective angiotensin II type 2 (AT2 ) receptor agonist on vascular remodeling. Design and Method: Inflammatory vascular remodeling was induced by polyethylene cuff-placement on the femoral artery in male 10 week-old C57BL/6J mice. Mice were pretreated with rosuvastatin (5 mg/kg/day or 0.5 mg/kg/day), and/or with C21 (10 μg/kg/day or 1 μg/kg/day) 2 weeks before cuff placement. Neointimal formation was investigated 14 days after operation. Cell proliferation, superoxide anion production and mRNA expressions of inflammatory cytokines were examined 7 days after cuff placement. Results: Neointimal formation was significantly attenuated by the treatment of higher dose of rosuvastatin or C21associated with the decreases in proliferating cell nuclear antigen (PCNA) labeling index, oxidative stress and the expression of inflammatory markers. Treatment with non-effective dose of rosuvastatin plus low dose of C21 inhibited PCNA labeling index, superoxide anion production, the mRNA expressions of NAD(P)H subunits and inflammatory markers associated with marked inhibition of neointimal formation. AT2 receptor mRNA expression was increased by administration of C21 at the dose of 10 μg/kg/day but not by C21 at the dose of 1 μg/kg/day or rosuvastatin, whereas angiotensin II type 1 receptor mRNA expression did not differ in each group. Conclusions: Combination treatment with rosuvastatin and AT2 receptor agonist exerted synergistic preventive effects on vascular remodeling; therefore, it could be a powerful approach to prevent vascular disease.